Longitudinal up‐regulation of endolymphatic hydrops in patients with Meniere's disease during medical treatment - Fukushima, Munehisa; Kitahara, Tadashi; Oya, Ryohei; Akahani, Shiro; Inohara, Hidenori; Naganawa, Shinji; Takeda, Noriaki (Laryngoscope Investigative Otolaryngology, 2017)
Objective/Hypothesis Meniere's disease (MD) is a common inner ear disease characterized by repeated episodic vertigo, fluctuating sensorineural hearing loss, and tinnitus. Its pathology is defined as endolymphatic hydrops (EH) in the inner ear and EH has been hypothesized to correlate with the clinical symptoms of MD. We presented the dynamics of in vivo EH in MD patients during medical treatments. Study Design Prospective, single‐arm repeated measures Methods Eleven MD patients were enrolled. All subjects prospectively underwent gadolinium‐enhanced inner ear magnetic resonance (MR) imaging and neuro‐otological testing before and after medical treatment. The volume of EH was quantitatively evaluated by processing MR images. All MD patients were administered continuous medication and followed up for more than 12 months. Results The frequency of vertigo episodes decreased in all patients and vestibular function decreased to 13–91% of the pre‐treatment level. The volume ratio of post‐treatment EH‐to‐pre‐treatment EH ranged from 1.01–3.22. The total volume of pre‐treatment EH was significantly correlated with cochlear symptom disease duration and the affected ear's hearing level. Conclusion EH in MD patients developed longitudinally with deterioration of inner ear function during medical treatment. The natural course of MD may progress with development of EH at least for a certain period. Level of Evidence 2b.